Prayer : does it make any difference? - Yancey, Philip (Grand Rapids, Mich. : Zondervan, 2006)
Author Yancey probes the most fundamental, challenging, perplexing, and deeply rewarding aspect of our relationship with God: prayer. In theory, prayer is the essential human act, a priceless point of contact between us and the God of the universe. In practice, prayer is often frustrating, confusing, and fraught with mystery. This book is an exploration of the mysterious intersection where God and humans meet and relate. Writing as a fellow pilgrim, Yancey explores such questions as: Is God listening? Why should God care about me? If God knows everything, what's the point of prayer? Why do answers to prayer seem so inconsistent and capricious? Why does God seem sometimes close and sometimes far away? How can I make prayer more satisfying?--From publisher description.
Part 1: Keeping company with God. Our deepest longing ; View from above ; Just as we are ; The God who is ; Coming together -- Part 2: Unraveling the mysteries. Why pray? ; Wrestling match ; Partnership ; What difference does it make? ; Does prayer change God? ; Ask, seek, knock -- Part 3: The language of prayer. Yearning for fluency ; Prayer grammar ; Tongue-tied ; The sound of silence -- Part 4: Prayer dilemmas. Unanswered prayer : whose fault? ; Unanswered prayer : living with the mystery ; Prayer and physical healing ; What to pray for -- Part 5: The practice of prayer. Prayer and me ; Prayer and others ; Prayer and God.
Includes bibliographical references (p. 335-350).
Keywords: Prayer -- Christianity